Cognitive Domain Analysis in the Context of the Merdeka Curriculum at Mts Negeri 1 East Lombok - Nabila Salsabila Iswar; Ajeng Maisaroh; Mohammad Asrori (Universitas Muhammadiyah Enrekang, 2023)
Assessment has the purpose to determine the attainment of educational objectives. There are three domains of assessment: cognitive, affective, and psychomotor. The cognitive domain focuses on assessing knowledge, comprehension, and intellectual thinking. Cognitive assessment tools can be designed through the utilization of authentic assessments, which replicate real-world situations or contexts. Authentic assessment methodologies offer a more precise means of evaluating a student's capacity to apply acquired concepts. This research had the purpose to investigate the development of cognitive assessment instruments within the independent curriculum at MTs Negeri 1 East Lombok. This qualitative research utilized a field-based approach, collecting data through teacher observations and interviews conducted at MTs Negeri 1 East Lombok. The data analysis process included data reduction, presentation, and inference. The outcomes suggested that cognitive domain assessment instruments in the independent curriculum should be in alignment with the learning objectives, integrate various question types, involve students in their development, and provide constructive feedback.